Negative plate, battery and electric equipment
By adopting a multi-layer structure design in the negative electrode sheet of the lithium-ion power battery, the particle size distribution of active materials in the sub-active layer is controlled, the lithium-ion liquid phase diffusion bottleneck is solved, the battery's continuous charging and fast charging capabilities are improved, and the overall performance is improved.
Patent Information
- Application Number
- CN202411925246.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-04-29
AI Technical Summary
Under high energy density conditions, the fast charging capability of lithium-ion power batteries is limited by the lithium-ion liquid phase diffusion bottleneck, resulting in the active material on the bottom layer of the negative electrode sheet being unable to fully embed lithium, resulting in abnormal expansion force and surface chromatography of lithium.
The negative electrode sheet with a multi-layer structure is adopted to control the particle size distribution of active materials in the sub-active layer to ensure that the D90/D50 ratio is small, prevent the dense accumulation of active materials, improve the porosity and pore size, thereby reducing the electrode tortuousness and improving the liquid mass transfer of the electrolyte.
It improves the battery's continuous charging capacity and fast charging capacity, avoids the increase in expansion force and surface lithium chromatography, and improves the overall performance of the battery.
Smart Images

Figure CN119905511A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and more specifically, to a negative electrode sheet, a battery and an electrical device. Background Art
[0002] A feasible way to improve the energy density of lithium-ion power batteries is to increase the surface density of the electrode dressing and increase the proportion of active materials in the battery. However, how to achieve high fast charging capabilities under high energy density conditions is a challenge. The thickness of high-surface-density negative electrode sheets often reaches 200-300 microns, and the liquid-phase diffusion of lithium ions becomes a bottleneck. During the charging and discharging process, the concentration difference of liquid-phase lithium ions in the thickness direction becomes larger, and ions tend to be embedded in the surface of the electrode. The active materials such as graphite at the bottom of the negative electrode cannot be fully embedded with lithium. This uneven characteristic leads to abnormally increased expansion force and surface lithium precipitation during fast charging. Summary of the invention
[0003] The present application aims to solve one of the technical problems in the related art at least to a certain extent. To this end, one purpose of the present application is to provide a negative electrode sheet having a lower electrode sheet tortuosity to improve the liquid phase mass transfer of the electrolyte in the battery.
[0004] In one aspect of the present application, the present application provides a negative electrode sheet. According to an embodiment of the present application, the negative electrode sheet includes: a negative electrode current collector; a negative electrode active layer, the negative electrode active layer is arranged on at least one surface of the negative electrode current collector, the negative electrode active layer includes n layers of stacked sub-active layers, the sub-active layer closest to the negative electrode current collector is defined as the first layer of the sub-active layer, and the sub-active layer farthest from the negative electrode current collector is defined as the nth layer of the sub-active layer, wherein, among the n layers of the sub-active layers, the particle size of the active material in the i-th layer of the sub-active layer satisfies D90 / D50≤1.5+1 / i, wherein n≥2 and is an integer, and 1≤i≤n and is an integer. Therefore, in the multi-layer sub-active layer, D90 / D50≤1.5+1 / i≤2.5, and it can be seen that the ratio of D90 / D50 is small, that is, the numerical values of D90 and D50 are small, indicating that the particle size distribution of the active material is narrow, which can effectively prevent the active material from producing a dense stacking effect. In this way, the porosity and pore size of the sub-active layer are relatively large, which is beneficial to reducing the electrode tortuosity and improving the liquid-phase mass transfer of the electrolyte in the battery, that is, it is beneficial to the liquid-phase migration of ions in the electrolyte, thereby improving the continuous charging capacity of the battery.
[0005] According to an embodiment of the present application, the particle size Dmax of the active material in the i-th sub-active layer is <H i , H i is the thickness of the i-th sub-active layer.
[0006] According to an embodiment of the present application, the particle size D50 of the active material in the i-th sub-active layer is i , the particle size D50 of the active material in the i+1th sub-active layer i+1 , D50 i+1 With D50 i Meets: D50 i+1 ≤D50 i .
[0007] According to an embodiment of the present application, the porosity P of the i-th sub-active layer is i , the porosity P of the i+1th sub-active layer i+1 , P i+1 With P i Satisfaction: P i+1 >P i .
[0008] According to an embodiment of the present application, the porosity P of the i-th sub-active layer is i The particle size D50 of the active material in the i-th layer i Satisfies: [In(D50 i )+2]*P i ≥1.3.
[0009] According to an embodiment of the present application, the active material is graphite.
[0010] According to an embodiment of the present application, the graphitization degree of graphite in the (i+1)th sub-active layer is less than or equal to the graphitization degree of graphite in the (i)th sub-active layer.
[0011] According to an embodiment of the present application, the degree of graphitization of graphite in the (i+1)th sub-active layer is ≤ the degree of graphitization of graphite in the (1)th sub-active layer - (the degree of graphitization of graphite in the (1)th sub-active layer - the degree of graphitization of graphite in the (n)th sub-active layer)*i / (n-1).
[0012] According to an embodiment of the present application, the graphitization degree of the graphite in the first sub-active layer is ≥ 94%, and the graphitization degree of the graphite in the nth sub-active layer is ≥ 90%.
[0013] According to an embodiment of the present application, D501 is 5 μm to 20 μm.
[0014] In another aspect of the present application, the present application provides a battery. According to an embodiment of the present application, the battery includes the negative electrode sheet described above. As a result, the battery has good continuous charging capability and fast charging capability. It is well known to those skilled in the art that the battery has all the features and advantages of the negative electrode sheet described above, and no further elaboration is given here.
[0015] In another aspect of the present application, the present application provides an electric device. According to an embodiment of the present application, the electric device includes the battery described above. As a result, the electric device has good continuous charging capability and fast charging capability. It is well known to those skilled in the art that the electric device has all the features and advantages of the negative electrode sheet described above, and no further elaboration is given here. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] The above and / or additional aspects and advantages of the present application will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0017] Figure 1 This is a schematic diagram of the structure of a negative electrode sheet in one embodiment of the present application;
[0018] Figure 2 is a schematic structural diagram of a negative electrode sheet in another embodiment of the present application;
[0019] Figure 3 is a scanning electron microscope image of the negative electrode active layer in Example 2;
[0020] Figure 4 is a scanning electron microscope image of the negative electrode active layer in control group 1;
[0021] Figure 5 It is a pore distribution diagram of the negative electrode active layer in Example 1 and the negative electrode active layer in the control group 1. DETAILED DESCRIPTION
[0022] The scheme of the present application will be explained below in conjunction with the embodiments. It will be appreciated by those skilled in the art that the following embodiments are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If no specific technology or conditions are indicated in the embodiments, the technology or conditions described in the literature in this area or the product specification are carried out. The reagents used or the instruments that do not indicate the manufacturer are all conventional products that can be obtained commercially.
[0023] The present application is described below with reference to specific embodiments. It should be noted that these embodiments are merely illustrative and do not limit the present application in any way.
[0024] In the negative electrode sheet of the battery, the active material particles self-accumulate to form a coherent channel, which helps to improve the liquid phase mass transfer capacity of the electrode. The pores in the negative electrode sheet can be divided into macropores and mesopores formed by the accumulation of active materials, where the macropores are at 1500-2500nm and the mesopores are at 500-1000nm. The macropores are mainly formed by the accumulation of active material D90 particles, while the mesopores are mainly formed by the accumulation of active material D50 particles. There is a certain interval between the macropores and the mesopores. The smaller the interval, the more conducive it is to reduce the tortuosity of the negative electrode sheet and improve the liquid phase mass transfer of the electrolyte. Based on this, the present application improves the liquid phase mass transfer of the electrolyte by controlling the D90 / D50 value in the negative electrode active layer, and further combines the multi-layer coating process. By changing the reaction activity of the active material in the thickness direction and the distribution ratio of the pores of the electrode sheet, the kinetic behavior of the negative electrode sheet can be regulated and optimized to improve its continuous charging ability.
[0025] Based on the above, in one aspect of the present application, the present application provides a negative electrode sheet. According to an embodiment of the present application, referring to Figure 1 and Figure 2 The negative electrode sheet includes: a negative electrode current collector 10; a negative electrode active layer 20, the negative electrode active layer 20 is arranged on at least one surface of the negative electrode current collector 10 ( Figure 1 and Figure 2 In the figure, only the case of setting the negative electrode active layer 20 on one side of the negative electrode current collector 10 is taken as an example. In the figure, large particles represent active materials D2 with a particle size of D90, and small particles represent active materials D1 with a particle size of D50). The negative electrode active layer 20 includes n stacked sub-active layers 21. The sub-active layer 21 closest to the negative electrode current collector 10 is defined as the first sub-active layer, and the sub-active layer 21 farthest from the negative electrode current collector 10 is defined as the nth sub-active layer, wherein, among the n sub-active layers 21, the particle size of the active material in the i-th sub-active layer satisfies D90 / D50≤1.5+1 / i, wherein n≥2 and is an integer, and 1≤i≤n and is an integer. Therefore, in the multi-layer sub-active layer, D90 / D50≤1.5+1 / i≤2.5, it can be seen that the ratio of D90 / D50 is small, that is, the numerical interval between D90 and D50 is small, indicating that the particle size distribution of the active material is narrow, which can effectively prevent the active material from producing a dense stacking effect. In this way, the porosity and pore size of the sub-active layer are relatively large, which is conducive to reducing the electrode tortuosity and improving the liquid-phase mass transfer of the electrolyte in the battery, that is, it is conducive to the liquid-phase migration of ions in the electrolyte (such as lithium ions in lithium-ion batteries), thereby improving the continuous charging capacity of the battery. In addition, in the thickness direction of the negative electrode sheet, the closer the D90 / D50 ratio of the sub-active layer is to the negative electrode current collector, the smaller it is, which can be more conducive to avoiding the dense stacking effect of the active material, and thus more conducive to reducing the electrode tortuosity and improving the liquid-phase mass transfer of the electrolyte in the battery, thereby improving the continuous charging capacity of the battery.
[0026] It should be noted that D50 is the particle size at the 50% point of the cumulative distribution of the particle number, and D90 is the particle size at the 90% point of the cumulative distribution of the particle number.
[0027] In some specific embodiments, two sub-active layers 21 are included, in which D90 / D50≤2.5 in the first sub-active layer, and D90 / D50≤1.5+0.5=2 in the second sub-active layer; in other specific embodiments, three sub-active layers 21 are included, in which D90 / D50≤2.5 in the first sub-active layer, D90 / D50≤1.5+0.5=2 in the second sub-active layer, and D90 / D50≤1.5+0.5=2 in the third sub-active layer. 50≤1.5+0.333=1.833; in some other specific embodiments, four sub-active layers 21 are included, in the first sub-active layer, D90 / D50≤2.5, in the second sub-active layer, D90 / D50≤1.5+0.5=2, in the third sub-active layer, D90 / D50≤1.5+0.333=1.833, in the fourth sub-active layer, D90 / D50≤1.5+0.25=1.75.
[0028] According to some embodiments of the present application, the particle size D501 of the active material in the first sub-active layer is 5 μm to 20 μm, such as 5 μm, 8 μm, 10 μm, 12 μm, 15 μm, 18 μm, 20 μm, etc. In this way, the particle size D90 of the active material can be calculated according to the requirement of D90 / D50≤1.5+1 / i. For example, if D501 is 14 μm, the particle size D901 of the active material in the first sub-active layer is ≤35 μm. If the particle size D502 of the active material in the second sub-active layer is 10 μm, the particle size D902 of the active material in the second sub-active layer is ≤20 μm.
[0029] According to some embodiments of the present application, the particle size D50 of the active material in the i-th sub-active layer is i , the particle size D50 of the active material in the i+1th sub-active layer i+1 , D50 i+1 With D50 i Meets: D50 i+1 ≤D50 i That is, in the direction away from the negative electrode current collector, the particle size of the active material in the sub-active layer shows a decreasing trend. In this way, in the direction away from the negative electrode current collector, the reaction activity of the active material in the sub-active layer gradually increases, thereby improving the fast charging performance of the battery and helping to obtain a negative electrode sheet structure that can take into account both short-term / continuous charging.
[0030] According to some embodiments of the present application, the particle size Dmax of the active material in the i-th sub-active layer is <H i , H iis the thickness of the i-th sub-active layer, that is, in the sub-active layer 21, the thickness of the sub-active layer is greater than the maximum particle size of the active material in the sub-active layer, so that the coating of the sub-active layer 21 can be better achieved.
[0031] According to some embodiments of the present application, the porosity P of the i-th sub-active layer is i , the porosity P of the i+1th active layer i+1 , P i+1 With P i Satisfaction: P i+1 >P i , that is, in the direction away from the negative electrode current collector 10, the porosity of the sub-active layer 21 gradually increases. In this way, the sub-active layer of the nth layer has the largest porosity, which can expose more active areas, so that the surface of the negative electrode active layer has a larger reactive active area, which can further improve the ability of lithium insertion and extraction. In this way, on the basis of ensuring good liquid phase mass transfer ability of the negative electrode sheet, the surface reaction activity of the negative electrode sheet can be further improved, that is, on the basis of ensuring good continuous charging ability of the battery, the fast charging ability of the battery can be further improved.
[0032] According to some embodiments of the present application, the porosity P of the i-th sub-active layer is i The particle size D50 of the active material in the i-th layer i Satisfies: [In(D50 i )+2]*P i ≥1.3. Thus, in the sub-active layer, a smaller D50 active material can be used to match a higher porosity, which can be more conducive to the negative electrode active layer to exert a higher kinetic performance, while improving the surface reaction activity and liquid phase mass transfer capacity of the negative electrode sheet. In some specific embodiments, in the first sub-active layer, the active material D501 is 14μm, and its porosity P1 is ≥28%; in the second sub-active layer, the active material D50 is 10μm, and its porosity P i ≥30%; in the third sub-active layer, the active material D50 is 5μm, and its porosity P i ≥36%.
[0033] According to some embodiments of the present application, the active material is graphite, which can provide good electrochemical performance for the negative electrode active layer.
[0034] The graphitization degree of graphite affects its pressure resistance. The higher the graphitization degree of graphite, the higher the degree of compaction of graphite and the lower the porosity. Conversely, the lower the degree of graphitization of graphite (such as amorphous carbon), the lower the degree of compaction of graphite and the higher the porosity.
[0035] According to some embodiments of the present application, the graphitization degree of the graphite in the i+1th sub-active layer is less than or equal to the graphitization degree of the graphite in the i-th sub-active layer, that is, in the direction away from the negative electrode current collector, the graphitization degree of the graphite in the sub-active layer is decreasing. In this way, in the direction away from the negative electrode current collector, the porosity of the sub-active layer is increasing, so that the liquid phase mass transfer capacity of the negative electrode sheet and the reactivity of the sub-active layer can be taken into account at the same time, so that the negative electrode sheet can have good liquid phase mass transfer capacity and reactivity of the surface sub-active layer at the same time.
[0036] According to some embodiments of the present application, the graphitization degree of graphite in the i+1th sub-active layer is ≤ the graphitization degree of graphite in the 1st sub-active layer - (the graphitization degree of graphite in the 1st sub-active layer - the graphitization degree of graphite in the nth sub-active layer) * i / (n-1). In this way, the graphitization degree of graphite in the multi-layer sub-active layer changes in a gradient, and the sub-active layer can better take into account the liquid phase mass transfer capacity of the negative electrode sheet and the reactivity of the sub-active layer at the same time, so that the negative electrode sheet can have good liquid phase mass transfer capacity and the reactivity of the surface sub-active layer at the same time.
[0037] According to some embodiments of the present application, the graphitization degree of the graphite in the first sub-active layer is ≥ 94%, and the graphitization degree of the graphite in the nth sub-active layer is ≥ 90%, thereby ensuring good electrochemical performance of the negative electrode active layer.
[0038] According to some embodiments of the present application, the negative electrode active layer may further include components such as a conductive agent and a binder in addition to the above-mentioned active materials.
[0039] In some embodiments, the binder can be selected from at least one of styrene-butadiene rubber (SBR), styrene-propylene rubber (SAR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), sodium carboxymethyl cellulose (CMC) and carboxymethyl chitosan (CMCS).
[0040] In some embodiments, the conductive agent may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0041] According to some embodiments of the present application, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, a copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0042] In another aspect of the present application, the present application provides a battery. According to an embodiment of the present application, the battery includes the negative electrode sheet described above. As a result, the battery has good continuous charging capability and fast charging capability. It is well known to those skilled in the art that the battery has all the features and advantages of the negative electrode sheet described above, and no further elaboration is given here.
[0043] According to some embodiments of the present application, the battery may be a lithium-ion battery.
[0044] According to some embodiments of the present application, the lithium-ion battery includes, in addition to the above-mentioned negative electrode sheet, a positive electrode sheet, an electrolyte and a separator.
[0045] In some embodiments, the positive electrode sheet includes a positive electrode current collector and a positive electrode active layer disposed on at least one side of the positive electrode current collector. In some specific embodiments, the positive electrode active layer includes components such as a positive electrode active material, a conductive agent, and a binder.
[0046] In some embodiments, the positive electrode active material may include at least one of the following materials: olivine-structured lithium-containing phosphates, lithium transition metal oxides, and their respective modified compounds. Examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (also referred to as NCM 333 )、LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM 523 )、LiNi 0.5 Co 0.25 Mn 0.25 O2 (also referred to as NCM 211 )、LiNi 0.6 Co 0.2Mn 0.2 O2 (also referred to as NCM 622 )、LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM 811 )), lithium nickel cobalt aluminum oxide (such as LiNi 0.8 Co 0.15 Al 0.05 O2) and its modified compounds, etc. Examples of lithium-containing phosphates with an olivine structure may include, but are not limited to, at least one of lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon.
[0047] In some embodiments, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.
[0048] In some embodiments, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0049] In some embodiments, the positive electrode current collector may be a metal foil, for example, an aluminum foil.
[0050] In some embodiments, the electrolyte includes an electrolyte salt and a solvent. In some embodiments, the electrolyte salt may be selected from lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bisfluorosulfonyl imide, lithium bistrifluoromethanesulfonyl imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalate borate, lithium dioxalate borate, lithium difluorobisoxalate phosphate and lithium tetrafluorooxalate phosphate. In some embodiments, the solvent may be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, ethylene carbonate, vinylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.
[0051] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.
[0052] In some embodiments, the material of the diaphragm can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The diaphragm can be a single-layer film or a multi-layer composite film, without particular limitation. When the diaphragm is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0053] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly by a winding process or a lamination process.
[0054] In another aspect of the present application, the present application provides an electric device. According to an embodiment of the present application, the electric device includes the battery described above. As a result, the electric device has good continuous charging capability and fast charging capability. It is well known to those skilled in the art that the electric device has all the features and advantages of the negative electrode sheet described above, and no further elaboration is given here.
[0055] According to some embodiments of the present application, electrical equipment may include but is not limited to mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains and other equipment.
[0056] Example
[0057] Embodiment 1 to Embodiment 8
[0058] The preparation method of a lithium-ion battery comprises:
[0059] Preparation of positive electrode sheet: Add positive electrode active material LFP, conductive agent CNT, and conductive carbon black to the prepared binder PVDF solution (NMP as solvent) with a solid ratio of 96:1:1:2, and stir for 2 hours to obtain positive electrode slurry. Evenly coat the slurry on a 13μm aluminum current collector and dry it to obtain a positive electrode active layer. The coating weight of the positive electrode active layer is 450g / m 2 The density of the positive electrode active layer after tableting is 2.6g / cm 3 .
[0060] Negative electrode preparation (double-layer coating):
[0061] Preparation of the first layer of negative electrode slurry: adding negative electrode active material graphite, conductive carbon black, SBR styrene-butadiene rubber, and CMC sodium carboxymethyl cellulose to water in a ratio of 97:1:1:1 and stirring for 2 hours to obtain the first layer of negative electrode slurry;
[0062] Preparation of the second layer of negative electrode slurry: adding negative electrode active materials graphite, conductive carbon black, SBR styrene-butadiene rubber, and CMC sodium carboxymethyl cellulose into water in a ratio of 97:1:1:1 and stirring for 2 hours to obtain the second layer of negative electrode slurry.
[0063] Preparation of the third layer of negative electrode slurry (coated or uncoated): Add negative electrode active materials graphite, conductive carbon black, SBR styrene-butadiene rubber, and CMC sodium carboxymethyl cellulose into water in a ratio of 97:1:1:1 and stir for 2 hours to obtain the third layer of negative electrode slurry.
[0064] Negative electrode active layer coating, the first layer of negative electrode slurry is added to the first layer negative electrode slurry dispersion tank, the second layer of negative electrode slurry is added to the second layer negative electrode slurry dispersion tank, the third layer of negative electrode slurry is added to the third layer negative electrode slurry dispersion tank, the tank body is connected to a double-layer or triple-layer coating die, the first layer of negative electrode slurry is extruded onto a 6μm copper foil through the coating die, and at the same time, the second layer of negative electrode slurry is extruded onto the first layer of negative electrode slurry through the coating die, or, further, the third layer of negative electrode slurry is extruded onto the second layer of negative electrode slurry through the coating die. After baking, a double-layer or triple-layer negative electrode active layer is obtained. Among them, the coating weight of the negative electrode active layer is 200g / m 2 The density of the negative electrode active layer after tableting is 1.6g / cm 3 .
[0065] Preparation of electrolyte: The electrolyte solvent was prepared according to the weight ratio of EC (ethylene carbonate): EMC (ethyl methyl carbonate): DMC (dimethyl carbonate): VC (vinylene carbonate) = 28:40:30:2, and the electrolyte salt was 1 mol / L LiFP6.
[0066] Diaphragm: Use 9μm polyethylene PE, one side is coated with a 2μm ceramic layer, and the ceramic layer is coated with a 2μm PVDF adhesive layer.
[0067] In an environment with a dew point below -30℃, stack the positive electrode sheet, separator, and negative electrode sheet in order, with the separator ceramic layer facing the positive electrode sheet. After obtaining the electrode assembly, use aluminum plastic film to package it, bake it at 90℃ for 24h, inject electrolyte, and then perform high-temperature infiltration, formation, sealing, aging, and capacity division to obtain the battery cell.
[0068] The parameters of the negative electrode active material graphite such as particle size and graphitization degree in Examples 1 to 8 can be seen in Table 1.
[0069] Control group 1
[0070] The steps for preparing the battery cell in Control Group 1 are basically the same as those in Example 1, except that the negative electrode sheet is prepared (double-layer coating):
[0071] The negative electrode active material graphite, conductive carbon black, SBR styrene-butadiene rubber and CMC sodium carboxymethyl cellulose were added into water in a ratio of 97:1:1:1 and stirred for 2 hours to obtain the negative electrode slurry.
[0072] Negative electrode active layer coating: negative electrode slurry is added to the negative electrode slurry dispersion tank, the tank body is connected to the coating die head, and the negative electrode slurry is extruded onto the 6μm copper foil through the coating die head. After baking, a single layer of negative electrode active layer is obtained. Among them, the coating weight of the negative electrode active layer is 200g / m 2 The density of the negative electrode active layer after tableting is 1.6g / cm 3 .
[0073] Parameter test method:
[0074] Particle size detection method: CP argon ion beam cutting is used to cut the negative electrode active layer into cross-sectional samples of 5*3mm each, >20 pieces, and SEM electron microscope scanning is used to obtain the cross-sectional information of each electrode piece (number of layers, thickness, particle size). The image is used to identify the cross-sectional area of each particle and calculate its diameter by equivalently converting it to a circle. Count >500 particles and obtain D50 and D90 based on the particle size distribution.
[0075] Porosity detection method: Like the particle size detection method, the cross-sectional area of the particles in the negative electrode active layer is summed to obtain the active material area of the negative electrode active layer, and the total area of the negative electrode active layer is calculated based on the statistical length and thickness of the negative electrode active layer. Porosity % = 1-active material area of the electrode layer / total area of the electrode layer.
[0076] Porosity distribution detection method: The original pore-mercury intrusion curve is obtained by mercury intrusion testing, and the following can be obtained: Figure 4 The pore pattern shown in the figure and the mercury intrusion method refer to GB T 21650.3-2011 standard for details.
[0077] Graphitization degree detection method: identify the thickness of each electrode layer by SEM, separate each graphite layer by CP argon ion beam cutting, extract graphite sample for XRD detection, calculate d002, graphitization degree = (d002-0.3354) / (0.344-0.3354)*100%.
[0078] Room temperature charging test method (with expansion force sensor): Taking the positive electrode LFP and the negative electrode graphite system as an example, at 25°C, the battery is discharged to 2V at a rate of 1C. After standing for 12 hours to stabilize, the battery is placed in the expansion force fixture and a restraining force of 2000N (pressure 33kpa) is applied, and the battery is charged to an upper limit voltage of 3.65V at a rate of 3C. Record the charging capacity and divide it by the battery's 1C discharge capacity to obtain the capacity retention rate; record the expansion force at the end of charging and subtract it from the initial restraining force to obtain the Δ expansion force.
[0079] Table 1
[0080]
[0081] In the table, “ / ” indicates that the structure and corresponding data are not present. In addition, in Example 2, because the second sub-active layer has a low degree of graphitization, its modulus is higher, it is harder, and the force transmission effect is better. Therefore, when the second sub-active layer is rolled, the pressure is transmitted to the first sub-active layer, resulting in a tighter stacking of the first layer and a lower porosity. Therefore, the porosity of the first sub-active layer in Example 2 is smaller than that of the first sub-active layer in Example 1.
[0082] The scanning electron microscope images of the negative electrode active layer in Example 2 and the negative electrode active layer in Control Group 1 can be seen in Figure 3 and Figure 4 ,exist Figure 3 The pore distribution of the negative electrode active layer in Example 2 is shown. It can be seen that the second sub-active layer has a larger porosity than the first sub-active layer. Figure 4 The pore distribution of the negative electrode active layer in the control group 1 is shown in FIG. 1 . It can be seen that the pore distribution of the first sub-active layer and the second sub-active layer is basically the same.
[0083] The pore distribution of the negative electrode active layer in Example 1 and the negative electrode active layer in Comparative Example 1 can be seen in Figure 5 , it can be seen that the negative electrode active layer in Example 1 has a lower tortuosity.
[0084] It can be seen from Examples 1 to 8 and Comparative Example 1 that reducing the particle size D90 of graphite in the second sub-active layer can improve the rate charging capability of the battery cell. This is because by reducing the D90 / D50 of the second sub-active layer relative to the first sub-active layer, the reaction activity of the graphite can be improved, the tortuosity of the negative electrode sheet can be reduced, the liquid phase mass transfer capacity can be improved, the capacity retention rate of the battery can be improved, and charging expansion can be reduced.
[0085] By comparing Examples 1, 2, 4 with Examples 3 and 8, it can be seen that by further reducing the degree of graphitization of the graphite in the second sub-active layer, the porosity of the second sub-active layer can be further increased, and the expansion can be reduced. The gradient porosity and gradient reaction activity can be taken into account to further improve the battery charging performance and improve the capacity retention rate.
[0086] By comparing Example 7 with Example 2, it can be seen that increasing the number of sub-active layers can form more continuous pores and particle size distribution, reduce expansion, further improve battery charging performance, and increase capacity retention.
[0087] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0088] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present application.
Claims
1. A negative electrode sheet, characterized in that: include: Anode current collector; A negative electrode active layer, the negative electrode active layer is arranged on at least one surface of the negative electrode current collector, the negative electrode active layer includes n layers of stacked sub-active layers, the sub-active layer closest to the negative electrode current collector is defined as the first sub-active layer, and the sub-active layer farthest from the negative electrode current collector is defined as the nth sub-active layer, Among the n-th sub-active layer, the particle size of the active material in the i-th sub-active layer satisfies D90 / D50≤1.5+1 / i, wherein n≥2 and is an integer, and 1≤i≤n and is an integer.
2. The negative electrode sheet according to claim 1, characterized in that: The particle size of the active material in the i-th sub-active layer is Dmax≤H i , H i is the thickness of the i-th sub-active layer.
3. The negative electrode sheet according to claim 1 or 2, characterized in that: The particle size D50 of the active material in the i-th sub-active layer i , the particle size D50 of the active material in the i+1th sub-active layer i+1 , D50 i+1 With D50 i Meets: D50 i+1 ≤D50 i .
4. The negative electrode sheet according to any one of claims 1 to 3, characterized in that: The porosity P of the i-th sub-active layer i , the porosity P of the i+1th sub-active layer i+1 , P i+1 With P i Satisfaction: P i+1 >P i .
5. The negative electrode sheet according to claim 4, characterized in that: The porosity P of the i-th sub-active layer i The particle size D50 of the active material in the i-th layer i Satisfies: [In(D50 i )+2]*P i ≥1.
3.
6. The negative electrode sheet according to any one of claims 1 to 5, characterized in that: The active material is graphite.
7. The negative electrode sheet according to claim 6, characterized in that: The graphitization degree of the graphite in the (i+1)th sub-active layer is less than or equal to the graphitization degree of the graphite in the (i)th sub-active layer.
8. The negative electrode sheet according to claim 7, characterized in that: The graphitization degree of graphite in the (i+1)th sub-active layer is ≤ the graphitization degree of graphite in the (1)th sub-active layer - (the graphitization degree of graphite in the (1)th sub-active layer - the graphitization degree of graphite in the (n)th sub-active layer) * i / (n-1).
9. The negative electrode sheet according to claim 7 or 8, characterized in that: The graphitization degree of the graphite in the first sub-active layer is ≥94%, and the graphitization degree of the graphite in the nth sub-active layer is ≥90%.
10. The negative electrode sheet according to any one of claims 1 to 9, characterized in that: D501 is 5μm~20μm.
11. A battery, characterized in that: The negative electrode sheet comprises the negative electrode sheet according to any one of claims 1 to 10.
12. An electrical equipment, characterized in that: Comprising the battery of claim 11.